Presentation of the research project: gender dimension in initial physical education teacher education in Portugal - Queirós, Telma Maria Gonçalves (2014)
Gender dimension exists across societies and therefore education. Hence certain learning areas in particular (e.g. Physical Education (PE)) are embedded with powerful gendered practices. Recent international research has shown that physical activities within the school curriculum contribute to reinforce and development of “gender-appropriate” behaviour often considered socially and culturally legitimate. In Portugal, this is also particularly visible in some studies which argued that teachers of PE may claim that they espouse equality of opportunity for all children, but their teaching behaviours and practices reveal entrenched sex stereotyping, based on historical constructions of sport and sense ‘notions about what boys and girls must do, i.e., what is suitable for girls and boys in PE. The present study aims to investigate within initial physical education teacher education (IPETE) in public universities of Portugal, how teacher concepts, beliefs, programs and practices contribute do gender construction. The sample consists of: (i) study plans and modules of Master Degree Programs on IPETE in all public universities in Portugal; (ii) directors of all this Master Degree Programs; (iii) teachers educators (supervisors and cooperative teachers (CT)) responsible for the supervision and orientation of the student teachers (ST) over the Supervised Teaching Practice in a university; (iv) ST who are attending the Supervised Teaching Practice in a university. The methodological option adopted is the qualitative approach. The data collected from different sources (i.e. observations, field notes, interviews with directors, teacher’s educators and ST) will be inductively analyzed using the QSR NVivo software for qualitative research.